A Review: Methodologies to Promote the Differentiation of Mesenchymal Stem Cells for the Regeneration of Intervertebral Disc Cells Following Intervertebral Disc Degeneration - Takashi Ohnishi; Kentaro Homan; Akira Fukushima; Daisuke Ukeba; Norimasa Iwasaki; Hideki Sudo (Cells, 2023)
Intervertebral disc (IVD) degeneration (IDD), a highly prevalent pathological condition worldwide, is widely associated with back pain. Treatments available compensate for the impaired function of the degenerated IVD but typically have incomplete resolutions because of their adverse complications. Therefore, fundamental regenerative treatments need exploration. Mesenchymal stem cell (MSC) therapy has been recognized as a mainstream research objective by the World Health Organization and was consequently studied by various research groups. Implanted MSCs exert anti-inflammatory, anti-apoptotic, and anti-pyroptotic effects and promote extracellular component production, as well as differentiation into IVD cells themselves. Hence, the ultimate goal of MSC therapy is to recover IVD cells and consequently regenerate the extracellular matrix of degenerated IVDs. Notably, in addition to MSC implantation, healthy nucleus pulposus (NP) cells (NPCs) have been implanted to regenerate NP, which is currently undergoing clinical trials. NPC-derived exosomes have been investigated for their ability to differentiate MSCs from NPC-like phenotypes. A stable and economical source of IVD cells may include allogeneic MSCs from the cell bank for differentiation into IVD cells. Therefore, multiple alternative therapeutic options should be considered if a refined protocol for the differentiation of MSCs into IVD cells is established. In this study, we comprehensively reviewed the molecules, scaffolds, and environmental factors that facilitate the differentiation of MSCs into IVD cells for regenerative therapies for IDD.